A highly sensitive method for detecting Cryptosporidium parvum oocysts recovered from source and finished water using RT-PCR directed to Cryspovirus RNA - Souza, Milena Sato de [UNESP]; O'Brien, Celia; Santin, Monica; Jenkins, Mark (Elsevier B.V., 2019)
Sensitive detection of Cryptosporidium oocysts is important because the protozoan can cause clinical infection in humans at extremely low numbers. In the present study, 1.5 x 10(2), 1.0 x 10(3), or 1.0 x 10(4)C. parvum oocysts were spiked into 101 of source or finished water in triplicate followed by recovery using Envirochek HV sampling capsules. One subsample of the recovered oocysts was analyzed by commercial immuno fluorescence assay (IFA), while a second subsample was subjected to DNA-RNA extraction, followed by RT-PCR using primers directed to the gene encoding Cryspovirus capsid. IFA analysis of Envirochek filter eluates of finished water detected oocysts at all 3 C. parvum oocyst doses, but only at the 1.0 x 10(3) and 1.0 x 10(4) doses in source water. Cryspovirus RT-PCR appeared to offer greater sensitivity than IFA because C. parvum oocysts were detected using this molecular technique in both source and finished water concentrates at all 3 spiking levels. A linear relationship was observed between log oocysts spiking dose and the relative intensity of the Cryspovirus RT-PCR signal for finished water, but not for source water. These data indicate that Cryspovirus RT-PCR is a sensitive method for detecting C. parvum oocysts in source and finished water.
Keywords: Cryptosporidium parvum; EPA Method 1623; RT-PCR; Cryspovirus